Strategy of Utilization of Air Side Idle Land at Raja Sisingamangaraja XII Airport - Marbun, Ardon; Iqbal Firdaus, Muhammad; Ade Suryobuwono, Abdullah (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This research is motivated by the existence of empty land in the airside area that is not utilized but still requires routine maintenance so that it requires operational costs. This study aims to analyze strategies that can be carried out to utilize idle airside land at Raja Sisingamangaraja XII Airport. The research method is qualitative. The informants in this study are informants who provide convenience to researchers in conducting analysis and obtaining research results regarding the strategy for utilizing idle airside land. Data collection methods consist of: observation (direct observation), interviews, and Focus Group Discussions, documentation. Interactive data analysis methods are used in research and data from the research results are validated. The results of this study indicate that one strategy that can be applied in utilizing idle airport side land is to be used as a means of generating solar power so that it can reduce operational costs and can also produce electrical energy that can be used by the airport and is environmentally friendly. Based on the results of the study, airport managers can continue to observe and utilize land in the airport area. In addition, it is also hoped that airport managers can supervise and maintain solar power plants that have been selected as one of the strategies for utilizing idle airside land.